MONOPOLAR ELECTROCAUTERY VERSUS ULTRASONIC DISSECTION OF THE GALLBLADDER FROM THE GALLBLADDER BED IN LAPAROSCOPIC CHOLECYSTECTOMY - Ramzanali, Shireen A A; Islam, Zia -ul-; Shah, Syed Sagheer Hussain (Journal of Ayub Medical College Abbottabad, 2013)
Background: Gold standard treatment for symptomatic gall stones is laparoscopic cholecystectomy (LC). Ultrasonically activated devices have been used for gall bladder dissection in LC. Harmonic scalpel (HS) is the leading ultrasonically cutting coagulation device offering surgeons important benefits. The main aim of our study was to compare the surgical outcomes of LC performed by HS to that performed by conventional mono-polar diathermy (electro-cautery). Methods: This prospective randomized study was conducted in surgical department of Jinnah Postgraduate Medical Centre, Karachi, during May-October 2013. During this period we selected 92 patients with symptomatic gallstones who underwent LC; these patients were randomly recruited into two groups using sealed opaque envelopes. Group A underwent gallbladder dissection from its bed using mono-polar diathermy, while on the other hand in Group B the dissection was carried out using harmonic scalpel. The outcomes like gallbladder perforation with bile spillage, intra-operative bleeding and operative time were assessed. Results: The harmonic scalpel (HS) usage in surgery results in shorter operative time, it also leads to less gallbladder injury, bile leakage and stone spillage (due to minimal lateralization of heat energy) not only this it also leads to less intra-operative blood loss. Conclusion: Harmonic scalpel is a new innovation in gallbladder surgery it has multiple functions like cutting, coagulation, coaptaion and cavitation which have made it safe, handy, effective and reliable instrument. Keywords: Gall stones, cholecystectomy, electrocautery, monopolar, gall bladder